Detection of endoscopic looping during colonoscopy procedure by using embedded bending sensors - Bruce M (Dove Medical Press, 2018)
Michael Bruce,1 JungHun Choi2 1Department of Mechanical Engineering, Ohio University, Athens, OH, USA; 2Department of Mechanical Engineering, Georgia Southern University, Statesboro, GA, USA Background: Looping of the colonoscope shaft during procedure is one of the most common obstacles encountered by colonoscopists. It occurs in 91% of cases with the N-sigmoid loop being the most common, occurring in 79% of cases. Purpose: Herein, a novel system is developed that will give a complete three-dimensional (3D) vector image of the shaft as it passes through the colon, to aid the colonoscopist in detecting loops before they form. Patients and methods: A series of connected links spans the middle 50% of the shaft, where loops are likely to form. Two potentiometers are attached at each joint to measure angular deflection in two directions to allow for 3D positioning. This 3D positioning is converted into a 3D vector image using computer software. MATLAB software has been used to display the image on a computer monitor. For the different configuration of the colon model, the system determined the looping status. Results: Different configurations (N loop, reverse gamma loop, and reverse splenic flexure) of the loops were well defined using 3D vector image. Conclusion: The novel sensory system can accurately define the various configuration of the colon during the colonoscopy procedure. Keywords: colonoscopy, endoscopy, loop, 3D vector image, intubation